Maternal exposure to dim light at night induces behavioral alterations in the adolescent and adult offspring Wistar rat - González-González, Shellye; Gutiérrez-Pérez, Mariana; Guzmán-Ruiz, Mara A.; Espitia-Bautista, Estefania; Pavón, Rosa María; Estrada-Rodríguez, Karla P.; Díaz-Infante R., Alejandro; Guadarrama Gándara, Cecilia G.; Escobar, Carolina; Guerrero-Vargas, Natalí N. (Frontiers in Physiology, 2025)
IntroductionAccess to electric light has exposed living organisms to varying intensities of light throughout the 24 h day. Dim light at night (DLAN) is an inappropriate signal for the biological clock, which is responsible for the circadian organization of physiology. During the gestational period, physiological adaptations occur to ensure a successful pregnancy and optimal fetal development. Environmental maternal conditions, such as disruptions of maternal circadian rhythms, could negatively affect offspring health. We have previously demonstrated that exposure of female Wistar rats to DLAN results in circadian, metabolic, and behavioral alterations. A relevant behavior during adolescence is social play, primarily regulated by the nucleus accumbens (NAc) which is crucial for the proper performance of important behaviors in adulthood. Throughout development, microglia are responsible for the remodeling of diverse brain regions via synaptic pruning. During adolescence, this process occurs within the NAc, where immune-mediated remodeling directly impacts social play behavior.MethodsThis study investigated the effects of maternal exposure to DLAN or a light-dark cycle (LD) before (5 weeks) and during the gestational period (21–23 days) on the metabolism and behavior of offspring in adolescence and adulthood. Body mass was measured every 5 days from postnatal day 1 (PN1) to PN25 and every 10 days from PN40 to PN90; food consumption was monitored weekly from PN40 to PN90. Social play behavior was evaluated at PN40. The quantification and morphology of microglia in the NAc were measured on PN30. An open field test was conducted at PN60, and anhedonia test was assessed at PN90.Results and discussion Male and female offspring from mothers exposed to DLAN showed increased body mass gain at PN25. DLAN male offspring had lower food consumption, while DLAN females exhibited increased food consumption. In social play behavior, no differences were found between DLAN and LD female offspring. In contrast, DLAN male offspring exhibited a significant decrease in social play behavior compared to LD animals, which was associated with higher numbers of microglia in the NAc that had more ramified morphology. Importantly, at PN90, DLAN offspring presented increased anxiety-like behaviors. These results demonstrate that DLAN exposure induces intergenerational behavioral alterations that persist until adulthood.